Small signal audio design - Self, Douglas (New York, NY : Routledge, 2024)
"Small Signal Audio Design is a highly practical handbook providing an extensive repertoire of circuits that can be assembled to make almost any type of audio system. This fully revised fourth edition offers wholly new content on internally balanced audio design, electret microphones, emitter-follower stability, microphony in capacitors, and much, much more. This book continues the engaging prose style familiar to readers, as you learn why mercury-filled cables are not a good idea, the pitfalls of plating gold on copper, and what quotes from Star Trek have to do with PCB design. Learn how to: make amplifiers with apparently impossibly low noise; design discrete circuitry that can handle enormous signals with vanishingly low distortion; transform the performance of low-cost-opamps; build active filters with very low noise and distortion, while saving money on expensive capacitors; make incredibly accurate volume controls; make a huge variety of audio equalisers; make magnetic cartridge preamplifiers that have noise so low it is limited by basic physics, by using load synthesis; sum, switch, clip, compress, and route audio signals; build simple but ultra-low noise power supplies; be confident that phase perception is not an issue. Including all the crucial theory, but with minimal mathematics, Small Signal Audio Design is the must-have companion for anyone studying, researching, or working in audio engineering and audio electronics"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Audio amplifiers -- Design and construction; Sound -- Recording and reproducing; Signal processing